Effect of Cu(II) ions on the enhancement of tetracycline adsorption by Fe3O4@SiO2-Chitosan/graphene oxide nanocomposite. (10th February 2017) - Huang, Binyan; Liu, Yunguo; Li, Bin; Liu, Shaobo; Zeng, Guangming; Zeng, Zhiwei; Wang, Xiaohua; Ning, Qimeng; Zheng, Bohong; Yang, Chunping
Highlights: Fe3 O4 @SiO2 -Chitosan/GO adsorbent (MSCG) was successfully prepared. MSCG exerts enhanced interaction with the tetracycline (TC). Well explained the role of Cu(II) as the bridge between TC and MSCG. Magnetic separation technology was used to separate MSCG with TC from aqueous solution. The regenerated MSCG exhibited excellent reusability for the adsorption of TC with and without Cu(II). Abstract: Fe3 O4 @SiO2 -Chitosan/GO (MSCG) nanocomposite was investigated by various techniques (SEM, TEM, XRD, VSM, FT-IR, XPS) for the removal of tetracycline (TC). Effects of pH, zeta potential and initial contaminant concentration were studied in detail. Four background cations (Na +, K +, Ca 2+ and Mg 2+ ) with a concentration of 0.01 M showed little influence on the TC adsorption at the studied pH range while the divalent heavy metal cation Cu(II) could significantly enhance the adsorption. The results indicated that the highest adsorption capacity of TC were 183.47 mmol/kg and 67.57 mmol/kg on MSCG with and without Cu(II), respectively. According to mechanism investigation for the adsorption of TC by pH impact study and XPS analysis, besides electrostatic interaction and π–π interactions, the Cu(II) also acts as a bridge between TC and MSCG, which significantly improve the adsorption of TC. This study provided valuable guidance and effective method for the removal of TC from aquatic environments.